PENGARUH DEBT TO EQUITY RATIO (DER), EARNING PER SHARE (EPS), DAN RETURN ON ASSET (ROA) TERHADAP HARGA SAHAM PT BANK CENTRAL ASIA TBK - Riva Miranda Putri; Asmalidar (Politeknik Negeri Medan, 2024)
This research is entitled the effect of Debt to Equity Ratio (DER), Earning Per Share (EPS), and Return On Assets (ROA) on the stock price of PT Bank Central Asia Tbk for the 2019-2023 period. The aim of this research is to find out whether these variables have an effect on stock price. The data used is secondary data obtained from financial reports of PT Bank Central Asia Tbk for 2019-2023. This research uses quantitative methods by carrying out several data processes, namely multiple linear abalysis tests, coefficient of determination, t test, and f test. The result obtained state that Debt to Equity Ratio (DER), Earning Per Share (EPS), and Return On Assets (ROA) do not significantly influence stock price either partially or simultaneously.